Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Dalam Melakukan Penanganan Tersedak Pada Anak Usia Toddler di Poli Anak Rumah Sakit Pusri Palembang : Penelitian - Rina Mardiana; Oscar Ari Wiryansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Choking is a common emergency in young children that can lead to serious complications, even death, if not addressed promptly and appropriately. Maternal lack of first aid knowledge is one of the biggest risk factors that worsen the situation. The aim of this study was to analyze the impact of health education on improving mothers' knowledge in dealing with choking in young children at the Children's Poly Pusri Palembang Hospital. The study used a pre-experimental design with a before-and-after test procedure with 37 mothers. Data were collected using questionnaires before and after the health education session. The Wilcoxon test was used to measure differences in knowledge levels before and after the intervention. The results of the study showed that mothers' knowledge improved significantly after the health education session (p = 0.000). Before the intervention, only 8.1% of respondents had a high level of knowledge, while this figure increased to 81.1% after the intervention. These results indicate that health education effectively improves mothers' knowledge of how to manage choking in children. These findings underscore the importance of training in healthcare facilities as a preventive strategy for pediatric emergencies.